Health impacts in a changing climate: an overview - Louis, Valérie R.; Phalkey, Revati (European physical journal special topics, 2016)
In the past decades the topic of climate change has been subjected to intense scientific scrutiny, and since the mid-1990’s it has become an increasingly political issue. Because of increased temperatures and more frequent and intense extreme weather events, the number of direct injuries and deaths will increase, along with infectious diseases, whether food, water or vector-borne; respiratory and cardiovascular diseases are expected to rise due to worsened air pollution and extreme heat. In a context of on-going environmental degradation, local food-producing systems, both marine and terrestrial, will be affected and the risk of malnutrition, especially in children, will increase. These impacts on health and livelihood are expected to be significant factors in the spread of regional social crises, potentially leading to forced migration, conflicts and increased poverty.The link between health and climate change operates through a variety of pathways that are now well established. In addition to taking climate mitigation measures, it will also be necessary to take adaptation measures, such as strengthening health systems, improving preparedness and developing early warning systems. There is now a broad scientific consensus on the issue and the science is sufficiently robust to enable a coordinated response to meet this global challenge.